Proteome Comparison Between Natural Desiccation-Tolerant Plants and Drought-Protected Caspicum annuum Plants by Microbacterium sp. 3J1 - García-Fontana, Cristina; Vilchez, Juan Ignacio; Manzanera, Maximino (Frontiers in Microbiology, 2020)
Desiccation-tolerant plants are able to survive for extended periods of time in the absence of water. The molecular understanding of the mechanisms used by these plants to resist droughts can be of great value for improving drought tolerance in crops. This understanding is especially relevant in an environment that tends to increase the number and intensity of droughts. The combination of certain microorganisms with drought-sensitive plants can improve their tolerance to water scarcity. One of these bacteria is Microbacterium sp. 3J1, an actinobacteria able to protect pepper plants from drought. In this study, we supplemented drought-tolerant and drought-sensitive plant rhizospheres with Microbacterium sp. 3J1 and analyzed their proteomes under drought to investigate the plant-microbe interaction. We also compare this root proteome with the proteome found in desiccation-tolerant plants. In addition, we studied the proteome of Microbacterium sp. 3J1 subjected to drought to analyze its contribution to the plant-microbe interaction. We describe those mechanisms shared by desiccation-tolerant plants and sensitive plants protected by microorganisms focusing on protection against oxidative stress, and production of compatible solutes, plant hormones, and other more specific proteins.